Asymmetrical distribution of the transcriptionally competent NORs in mitosis - Kalmárová, Markéta; Kovácik, Lubomír; Popov, Alexey; Testillano, Sánchez Pilar; Smirnov, Evgeny (Journal of structural biology, 2008)
Ribosomal genes are organized in clusters termed Nucleolus Organizer Regions (NORs). Essential components of the RNA polymerase I transcription machinery, including Upstream Binding Factor (UBF), can be detected on some NORs during mitosis; these NORs, termed competent, are believed to be transcriptionally active during interphase. In cultured mammalian cycling cells, the number of competent NORs, and their distribution among the different chromosomes, does not vary significantly in the sequential cell cycles. In this work we investigate whether this stable state is achieved by equal distribution of competent NORs during cell division. To answer this question we first studied the state of NORs in telophase HeLa and LEP cells. In both cell lines we found a small but significant difference between the emerging daughter cells in the number of UBF-loaded NORs. To reveal the cause of this difference, we followed the fate of individual NOR using HeLa derived cell line stably expressing UBF-GFP. We demonstrated that some NORs in metaphase are "asymmetrical", i.e. they lack the signal of competence on one of the sister chromatids. Regular presence of such NORs can account for the difference in the number of competent NORs obtained by the daughter cells emerging in mitosis.
Keywords: Transcription, Genetic; buněčné linie; Chromatids; genetická transkripce; Mitosis; Cell Line; mitóza; Animals; Nucleolus Organizer Region; lidé; Pol1 Transcription Initiation Complex Proteins; chromatidy; transkripční iniciační komplex Pol1 - proteiny; organizátor jadérka; zvířata; Humans